Issues of Synonymy in the Works of Armenian Grammarians of the Middle Ages - Hovhannisyan, Nazik (Bulletin of Yerevan University B: Philology, 2023)
Synonymy is considered an indicator of the development of a language, and is naturally characteristic of all languages. The problem of synonymy is one of the most important in modern linguistics: as noted in the linguistic literature, at the present stage in the new scientific paradigm, researchers again and again return to the analysis of synonymous relations. This is due to the fact that synonymy is the philosophical side of the language. And in this sense, the approaches of the Armenian grammarians of the Middle Ages to the problem are characteristic from the point of view of clarifying the principles for compiling the handwritten dictionaries of synonyms (and their synonymic rows) created at that time. In the works of Armenian grammarians of the Middle Ages, the term "estates" was used for the concept of "synonym", which is a tracing paper from the Greek language, and the concept of "synonymy" was explained based on the teachings of philosophers and grammarians. The Armenian interpreters of "The Art of Grammar" by Doinisiоs of Thrace (David the Philosopher, Grigor Magistrоs, Yesai Nchetsi, Hovhannes Yerznkatsi and others), distinguishing the grammatical and philosophical meanings of the word, note that grammarians call "synonym" "verbosity", which is called the same the subject in various words, and philosophers - "estates", which are the names of various homogeneous concepts. Having little disagreement in the definition, Armenian grammarians of the Middle Ages unanimously believe that synonyms are words that comprehensively characterize an object, a phenomenon without semantic restriction or differentiation of semantic-functional relations.